DOMESTIFIKASI PEREMPUAN SAMIN DALAM KHASANAH MASYARAKAT ISLAM MODERN - Mukodi Mukodi; Afid Burhanuddin (IAIN Ponorogo, 2015)
Abstract: The dominance is a term that is owned by a variety of entities ranging from the lowest social strata up to those who have the highest power in public domain, even in the global public organization. The domination of the lowest domain up to the highest one can be transformed into a variety of issues including the role of someone in the public domain. Problems will arise when the role of men are much more dominant than women as shown in Samin community in Blora. Based on the concept of gender, this study tried to dismantle and explore the myths of Samin community and the commodity of Saminisme in Blora. The women of Samin were still placed as a sub-ordinate of men, that is, the Samin community in the village of Kelopo Dhuwur, called Wong Sikep (people of Sikep); Wong Samin who, in a particular level, still showed strong patriarchal culture in daily life, especially the issue of the concept of matchmaking in marriage and marriage itself. This condition was as a result of low level of their education which led to weakness of involvement of Samin women in public spaces. The local culture of this community had constructed domestication of women. Samin women's empowerment efforts had been done in two ways by its stakeholders, namely, Samin myth demolition and removal Saminisme commodities. The success and the positive effect of these two efforts had reached their attainment, although the results still showed the minimum ideal outcome.الملخص :إن موضوع